The American Revolution : an intimate history - Ward, Geoffrey C.; Burns, Ken, 1953- (Alfred A. Knopf, 2025)
From the award-winning historian and filmmakers of The Civil War, Baseball, Jazz, The Roosevelts, and others: a richly illustrated, human-centered history of America's founding struggle-expanding on the landmark, six-part PBS series to be aired in November 2025"From a small spark kindled in America, a flame has arisen not to be extinguished." -Thomas PaineIn defeating the British Empire and giving birth to a new nation, the American Revolution turned the world upside down. Thirteen colonies on the Atlantic coast rose in rebellion, won their independence, and established a new form of government that radically reshaped the continent and inspired independence movements and democratic reforms around the globe.The American Revolution was at once a war for independence, a civil war, and a world war, fought by neighbors on American farms and between global powers an ocean or more away. In this sumptuous volume, historian Geoffrey C. Ward ably steers us through the international forces at play, telling the story not from the top down but from the bottom up-and through the eyes of not only our "Founding Fathers" but also those of ordinary soldiers, as well as underrepresented populations such as women, African Americans, Native Americans, and American Loyalists, asking who exactly was entitled to life, liberty, and the pursuit of happiness.Enriched by guest essays from lauded historians such as Vincent Brown, Maya Jasanoff, and Alan Taylor, and by an astonishing array of prints, drawings, paintings, texts, and pamphlets from the time period, as well as newly commissioned art and maps-and woven together with the words of Thomas Paine- The American Revolution reveals a nation still grappling with the questions that fueled its remarkable founding.